Study on Diabetic Rats Comparing the Effects of Sitagliptin and Probiotics on Serum Glucose - Naghmana Lateef, Irum Rehman, Muhammad Tahir, Imran Mehboob Baig, Arjumand, Fayaz Ahmed Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Probiotics were compared to Sitagliptin in this research in order to see whether they might lower blood glucose levels in diabetic rats more effectively. Study Design: Quasi experimental study Place and Duration: Fatima Jinnah Medical University Lahore. Jan, 2021 to June, 2021 Methods: There were 80 male rats were presented in this study. We used Streptozotocin to inflict diabetes in rats, and after one week, the results were validated by measuring Fasting Blood Glucose (FBG) (>7 mmol/L was termed diabetic). Rats were divided in four groups. Group I had 20 diabetic control rats, group II had 20 rats and received probiotics (250 mg/Kg), group III received sitagliptin (10 mg/Kg) among 20 rats and group IV received combination of probiotics and sitagliptin. Blood glucose was measured at baseline and after 6-weeks. Results among all groups were compared. SPSS 24.0 was used to analyzed all data. Results: We observed that rats given probiotics in group-II saw a substantial drop in their fasting blood glucose levels, with an effectiveness that was on par with that of rats given sitagliptin in group-III (p 0.05). Sitagliptin and probiotics had a synergistic impact in group IV that was stronger (p<0.05) than either of their individual effects in groups II and III. Conclusion: We concluded that Sitagliptin plus Probiotics lowers diabetic rats’ blood glucose more than individual medicines. Probiotics reduce fasting blood glucose in diabetic rats like Sitagliptin. Diabetes treatment can include probiotics. Keywords: Diabetes mellitus, Fasting blood glucose, Sitagliptin, Probiotics, Rats